PROFESSIONAL TRAINING OF HUMANITIES TEACHERS IN POSTGRADUATE EDUCATION: REFLEXIVE PARADIGM - Сєнчина, Н. Г. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is dedicated to revealing the essence of professional training of humanities teachers in conditions of postgraduate education to realize reflexive activity. As a result of the retrospective analysis of goals and objectives of the Ukrainian postgraduate teachers’ education, the shift of educational accents from cognitive to personal has been proved, and the need for implementing a reflexive approach in the educational process has been substantiated. Basic paradigmatic characteristics of modern postgraduate pedagogical education have been revealed (dominance of axiological and sense-making components in the content of education, consideration of teacher’s professionalism from the reflexive perspective, reliance on empirical professional and social experience of trainees). Pedagogical reflection is viewed as a complex psychological phenomenon, manifested in the teacher’s ability to take an analytical position in relation to his/her activities. It has been proved that the effective development of professional pedagogical reflection in postgraduate education is possible provided that reflexive mechanisms of activity are used in practice, presented in the form of reflexive techniques designed on the basis of the reflexive didactic method. Reflexive techniques in postgraduate education provide an optimal level of professional and personal development. A significant part of reflexive techniques is realized in group forms of activity, the most effective of them are reflexive workshops